Dian Fahriani ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN MENURUT STANDAR AKUNTANSI KEUANGAN DAN UNDANG – UNDANG PERPAJAKAN CV JATAYU DI SURABAYA : Program Studi Akuntansi, Universitas Nahdlatul Ulama Sidoarjo *e-mail : dianfahriani87@gmail.com - Dian Fahriani (GREENOMIKA, 2019)
Income and costs are important components of financial statements. The accounting treatment in recognizing the existence of income and costs greatly influences the fairness of the financial statements, so that conformity in the application of the Financial Accounting Standards and Taxation Law is very necessary. Tax is an emphasis on the transfer of wealth to the economic impact that is generated. The people as taxpayers in the government side and also those who will receive tax payments. This research is to analyze the accounting policies and taxes applied by CV Jatayu in connection with the construction contract. The analytical method used is descriptive analysis where the data is reviewed and then analyzes based on existing theories to provide an actual picture in terms of recognition of cost and tax revenues in the construction contract business field. The results of the study were obtained, CV Jatayu had applied PSAK No. 34 on Accounting for Construction Services by using completion percentages based on job progress and Government Regulation No. 51 of 2008 concerning Income Tax on Construction Services Business. Companies need a standard and effective budgeting and budgeting system so that they can estimate income with costs and according to progress progress in the completion of work should also always take into account indirect costs that do not arise directly related to the project and increase worker resources in evaluating progress progress the project so as not to experience a mismatch of progress with the income received.